Effect of Bank Lending on Inflation in Nepal - Dhungana, Neelam Timsina; Pradhan, Radhe Shyam (Journal of Advanced Academic Research, 2018)
This study examines the effect of commercial bank lending on inflation in Nepal. The study has conducted correlation and regression analysis using panel data of twenty four commercial banks during the period of 1996 -2015. The empirical results show that bank lending has positive effect on the inflation in Nepal. The study implies that central bank willing to contain inflation should curtail excessive bank lending on unproductive and speculative sector.